The civic muse : music and musicians in Siena during the Middle Ages and the Renaissance - D'Accone, Frank A. (University of Chicago Press, 1997)
Siena, blessed with neither the aristocratic nor the ecclesiastical patronage enjoyed by music in other northern Italian centers like Florence, nevertheless attracted first-rate composers and performers from all over Europe. As Frank A. D'Accone shows in this scrupulously documented study, policies developed by the town to favor the common good formed the basis of Siena's ambitious musical programs. Based on decades of research in the town's archives, D'Accone's The Civic Muse brilliantly illuminates both the sacred and the secular aspects of more than three centuries of mu.